Palbebral anthrax - Çelebi, S; Aykan, Ü; Alagöz, G; Esmerligil, S (Wichtig Editore, 2001)
PURPOSE. Anthrax is a rare infection transmitted to humans from animals or animal products. In cutaneous anthrax it may produce lesions of the eyelids which can lead to cicatricial ectropion. METHODS. We examined three women and five men with anthrax of the eyelids. Intravenous penicillin G was used alone as therapy. RESULTS. All patients presented with a localized itchy erythematous papule of the eyelid. A necrotising ulcer formed in each case, resulting in black eschar. The lesions resolved, with only mild cicatrization of the eyelid in all the patients. CONCLUSIONS. Anthrax is primarily an infectious disease of domestic animals but it is also seen in humans. Eyelids are rarely affected but cutaneous anthrax should be considered in any patient with a painless ulcer or black eschar who has a history of exposure to animals.
Keywords: cutaneous anthrax; eyelids; black eschar; cicatricial ectropion